1996
DOI: 10.1056/nejm199612053352302
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radio-Frequency Neurotomy for Chronic Cervical Zygapophyseal-Joint Pain

Abstract: In patients with chronic cervical zygapophyseal-joint pain confirmed with double-blind, placebo-controlled local anesthesia, percutaneous radio-frequency neurotomy with multiple lesions of target nerves can provide lasting relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
526
1
8

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 781 publications
(560 citation statements)
references
References 19 publications
(22 reference statements)
23
526
1
8
Order By: Relevance
“…Two studies reported some subsiding pain and numbness associated with the procedure [60,92]. The symptoms were more common and lasted longer in the radiofrequency lesion group.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Two studies reported some subsiding pain and numbness associated with the procedure [60,92]. The symptoms were more common and lasted longer in the radiofrequency lesion group.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Yang and King [30] observed that the lumbar facet joint under compression could cause the capsule to stretch. Clinically, facet denervation has long been employed in the management of cervical, thoracic and low-back pain [4,17,22,24 Abstract Facet joint capsules (FJC) may experience large mechanical deformation under spine motion. There has been no previous quantitative study of the relationship between capsular strain and sensory nerve activation in spine FJC in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Studies support the idea that RF denervation is a treatment of choice for initial pain relief; however, it does not produce permanent pain relief because the nerve eventually regenerates, usually within 12-18 months (North et al, 1994). Lord et al found the median time of return to 50% of pre-procedure pain was 263 days (Lord et al, 1996). Dreyfuss et al found that pain relief may last for about 12 months (Dreyfuss et al, 2000).…”
Section: Anatomy and Pathogenesis Of Facet Joints Painmentioning
confidence: 99%